Volunteerism declined among university students: why do they not volunteer? - Normah, Awang Noh; Lukman@Zawawi, Mohamad (2020)
In this emerging economy, volunteerism has being part of important activities in many countries. It is also contributed towards the national development in producing proactive people to contribute volunteering towards community. It is one of the fundamental social activities which could be able to make our society and living condition in harmony, peace, and enjoyment. Volunteerism as an activity, is not money-oriented, but it benefitted to individual or group receiver in community and volunteers themselves. It is an altruistic activity. Globally, volunteerism has been considered a substantial development of the state, as it almost all the times enhance the social welfare system and provides help for the needed people in society. Even though it has been highly recognised as one of the influential factors for social development in many countries, unfortunately, the involvement of people in volunteerism is lately reported declined, particularly among university students. The declining participation of university students in volunteerism activity is mainly as a result of a hectic schedule, financial problem and the distance of the activity that is too far away from campus. Other factors mentioned are mobility-related problems, have no suitable time, health problems, have no required skill, and focusing only on academic achievement.